(untitled) (ETIMA, 2024)
This research paper thoroughly examines the fundamental principles and design concepts of molten salt thermal energy storage systems, focusing on the critical role of materials selection in choosing the appropriate material for the application. We also discuss the basic design components of these systems when integrated with renewable technology and classify practical systems by their applications. Based on our analysis, we conclude that solar technologies with molten salt storage systems are particularly promising for practical implementation, and the two-reservoir type system utilizing the sensible heat storage method of molten salt is regarded as the most commercially viable and mature electrothermal storage system available. Solar salt is also considered the best choice for these systems due to its low cost and high energy density. The idea of retrofitting fossil fuel plants with molten salt storage systems is also mentioned. Overall, molten salt thermal energy storage systems have the potential to play a crucial role in future energy systems, and further research and development in this field is essential for maximizing the potential of these systems and achieving a sustainable energy future.